The harem midwife : a novel - Rich, Roberta (Gallery Books, 2014)
"Hannah and Isaac return in this opulent, riveting, and suspenseful tale--a continuation of Roberta Rich's thrilling debut The Midwife of Venice. The Imperial Harem, Constantinople, 1579: Hannah and Isaac Levi, Venetians in exile, have set up a new life for themselves in Constantinople. Isaac runs a newly established business in the growing silk trade, while Hannah, the best midwife in all of Constantinople, plies her trade within the opulent palace of Sultan Murat III, tending to the thousand women of his lively and infamous harem. But one night, when Hannah is unexpectedly summoned to the palace, she's confronted with Zofia, a poor Jewish peasant girl who has been abducted and sold into the sultan's harem. The sultan favors her as his next conquest and wants her to produce his heir, but the girl just wants to return to her home and the only life she has ever known. Will Hannah risk her life and livelihood to protect this young girl, or will she prioritize her high esteem in the eye of the sultan? An adventurous, opulent and deliciously exciting read, peopled with fascinating, unforgettable characters (a court eunuch; the calculating sultan's mother-in-law; the beguiling harem ladies; and a very mysterious young beauty from Venice who shows up on Hannah's doorstep, causing much havoc), this novel is sure to please fans of The Midwife of Venice and extend Roberta's reputation as a beloved historical fiction author"--